2022
DOI: 10.5603/pjnns.a2021.0072
|View full text |Cite
|
Sign up to set email alerts
|

Neuro-COVID-19: an insidious virus in action

Abstract: Introduction:The punishing effect of the pandemic outbreak of the disease termed COVID-19 (coronavirus disease-19) caused by severe acute respiratory syndrome coronavirus type 2 (SARS-CoV-2) impelled the author to gather the facts about the nature of this new pathogen. The aim of this paper was to discuss the mechanisms involved in the pathogenesis of neurological complications during the course of COVID-19. State of the art:Neurological symptoms, such as impairment of taste or smell, headache, nausea and/or a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 106 publications
(129 reference statements)
0
24
0
Order By: Relevance
“…It has been confirmed that the coronavirus can penetrate different areas of the nervous system. Several mechanisms and routes to cross the BBB and spread within the CNS have been proposed, including virus affinity to ACE2 [14,28,29]. Some of these hypotheses assume that SARS-CoV-2 travels along the olfactory or trigeminal route [30], similarly to some neurotropic variants of the influenza virus [31].…”
Section: Sars-cov-2 Tissue Distributionmentioning
confidence: 99%
“…It has been confirmed that the coronavirus can penetrate different areas of the nervous system. Several mechanisms and routes to cross the BBB and spread within the CNS have been proposed, including virus affinity to ACE2 [14,28,29]. Some of these hypotheses assume that SARS-CoV-2 travels along the olfactory or trigeminal route [30], similarly to some neurotropic variants of the influenza virus [31].…”
Section: Sars-cov-2 Tissue Distributionmentioning
confidence: 99%
“…This study included 35 patients with the mean age of 65.5 ± 13.9 years. Neurological manifestations comorbid with COVID-19 were the reason for admission in the great majority of patients (31/35; 88.6%) and included: altered mental status (18 patients), seizures (eight patients), stroke (3), headache (1), subarachnoid haemorrhage (1), and posterior reversible encephalopathy syndrome (1). Almost all patients (32/35; 91.4%) had at leastone comorbidity.…”
Section: Patientsmentioning
confidence: 99%
“…Neurological symptoms and signs have been reported in the majority of patients with COVID-19 [1]. While clinical seizures affect only a small proportion of patients, electroencephalographic (EEG) abnormalities have been reported in 88-96% of cases, with generalised background slowing being the most frequent finding [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Observations to date suggest that most people complain of nervous system disorders. It is estimated that the so-called neuro-COVID affects between 62 and 70% of patients [119][120][121]. One recently published study analysed data from almost 1.2 million patients who contracted the coronavirus between 20 January 2020 and 13 April 2022 [61].…”
Section: Current Challenges and Future Perspectivesmentioning
confidence: 99%